2015
DOI: 10.1093/ajh/hpv104
|View full text |Cite
|
Sign up to set email alerts
|

Association of Post-Saline Load Plasma Aldosterone Levels With Left Ventricular Hypertrophy in Primary Hypertension

Abstract: In patients with hypertension, aldosterone levels measured after intravenous saline load are related to LV mass independent of age, body mass, and blood pressure, suggesting that limited ability of salt to modulate aldosterone production could contribute to LVH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Recently, in 90 untreated patients with primary hypertension we have reported an independent association of plasma aldosterone levels measured after an intravenous saline load with LVMI. 33 This finding suggested that a relatively inadequate ability of salt to suppress aldosterone secretion could contribute substantially to LV hypertrophy. du Cailar et al 34 evaluated 182 previously untreated hypertensive patients who were treated for 3 years with either angiotensinconverting enzyme inhibitors or angiotensin II receptor blockers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in 90 untreated patients with primary hypertension we have reported an independent association of plasma aldosterone levels measured after an intravenous saline load with LVMI. 33 This finding suggested that a relatively inadequate ability of salt to suppress aldosterone secretion could contribute substantially to LV hypertrophy. du Cailar et al 34 evaluated 182 previously untreated hypertensive patients who were treated for 3 years with either angiotensinconverting enzyme inhibitors or angiotensin II receptor blockers.…”
Section: Discussionmentioning
confidence: 99%
“…* Value is calculated without aldosterone antagonists. Beta blocker, n (%) 17 (53) 4 (12) 19 (57) 6 (18) Calcium channel blocker, n (%) 18 (56) 10 (31) 20 (61) 11 (33) ACE inhibitor, n (%) 11 (34) 7 (22) 14 (42) 5 (15) Angiotensin receptor blocker, n (%) 8 (25) 3 (9) 7 (21) 4 (12) Alpha blocker, n (%) 4 ( …”
Section: Discussionmentioning
confidence: 99%
“…In 182 hypertensive patients who were treated for 3 years with either angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers, du Cailar et al observed a direct relationship of the percentage change in ventricular mass with the absolute changes in urinary sodium and plasma aldosterone levels [ 52 ]. In 90 essential hypertensive patients free of clinically relevant cardiovascular complications, aldosterone levels measured after intravenous saline load were found to be independently related to left ventricular mass, suggesting that limited ability of salt to modulate aldosterone production could contribute to ventricular hypertrophy [ 53 ]. In 21 patients with primary aldosteronism, Pimenta et al found that urinary sodium independently predicts left ventricular mass [ 54 ].…”
Section: The Contribution Of Salt To Aldosterone-related Cardiac Dmentioning
confidence: 99%
“…It has also been shown that the post-SIT PAC is associated with the left ventricular mass, independent of age, body mass index, and BP. 22 It is possible that patients with suppressible aldosterone secretion have a milder phenotype and would not benefit from surgery. However, the post-SIT PAC was not associated with the outcome of adrenalectomy in our study.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%